Expanded graphite-based composite negative electrode material and preparation method and application thereof

By preparing expanded graphite-based composite anode material, the problems of low capacity and poor rate performance of graphite anode material are solved, and a battery anode material with high capacity, stable cycle and good rate performance are achieved.

CN119905592APending Publication Date: 2025-04-29ZHANJIANG JUXIN NEW ENERGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510051426.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing graphite anode materials have problems with low capacity and poor rate performance in lithium-ion batteries, mainly due to the low theoretical capacity of natural graphite and the large diffusion resistance of lithium ions.

Method used

The expanded graphite-based composite negative electrode material is used to mix expanded graphite and aromatic hydrocarbon materials by ball milling, and polymerization and carbonization are carried out in the reactor to generate expanded graphite/amorphous carbon composite material. Subsequently, by crushing, adsorption of transition metal ions and vulcanization treatment, an expanded graphite/amorphous carbon/transition metal sulfide composite is formed and the surface is coated with a hard carbon layer.

Benefits of technology

The stability of expanded graphite is significantly improved, and the first discharge capacity, cycle performance and rate performance of expanded graphite-based composite anode material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240070830000111
    Figure BDA0005240070830000111
Patent Text Reader

Abstract

The invention provides an expanded graphite-based composite negative electrode material as well as a preparation method and application thereof. The preparation method comprises the following steps: firstly, enabling an aromatic hydrocarbon substance with a low melting point to enter an interlayer structure in expanded graphite in a molten state; amorphous carbon (a product obtained by carbonizing a polymer formed by polymerization of aromatic hydrocarbon substances) is firmly fixed between expanded graphite layers while polymerization of the aromatic hydrocarbon substances is catalyzed by boron trifluoride, and a third-stage pore structure and a fourth-stage pore structure of the expanded graphite are exposed through crushing, so that the specific surface area of the expanded graphite is increased; and then soaking in a metal salt solution containing transition metal elements. The expanded graphite-based composite negative electrode material prepared by the method has excellent first discharge capacity, cycle performance and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular relates to an expanded graphite-based composite negative electrode material and a preparation method and application thereof. Background Art

[0002] With the continuous development of new energy vehicles, energy storage and other industries, the new energy battery industry has been continuously upgraded, and the requirements for battery charging and discharging performance and energy density have been continuously improved. As one of the four key materials of the battery, the negative electrode material has a significant impact on the battery's energy density, cycle performance, charge and discharge rate, and low-temperature discharge performance. Graphite is regarded as the most promising negative electrode material for lithium-ion batteries because of its relatively high capacity and conductivity, and its low price and easy availability. Despite this, there are still some technical bottlenecks in the application of graphite negative electrodes in lithium-ion batteries, such as: (1) The theoretical capacity of natural graphite is only 372mAh·g -1 , which results in a lower capacity of lithium-ion batteries; (2) The graphite layer spacing is small, only 0.335nm, which results in a larger diffusion resistance of lithium ions and unsatisfactory diffusion kinetics, making it impossible to achieve ideal rate performance. Summary of the invention

[0003] In order to improve the problems of low capacity and poor rate performance of graphite negative electrode materials in the prior art, the present invention provides an expanded graphite-based composite negative electrode material and a preparation method and application thereof. The expanded graphite-based composite negative electrode material prepared by the method can have excellent first discharge capacity, cycle performance and rate performance.

[0004] The present invention provides the following technical solutions:

[0005] A method for preparing an expanded graphite-based composite negative electrode material, the method comprising the following steps:

[0006] (1) ball-milling and mixing expanded graphite and aromatic hydrocarbons, then adding the mixture into a reactor for polymerization reaction, while introducing boron trifluoride gas into the reactor, introducing nitrogen into the reactor after the polymerization reaction, and performing carbonization treatment under a nitrogen atmosphere to prepare an expanded graphite / amorphous carbon composite material;

[0007] (2) crushing and classifying the expanded graphite / amorphous carbon composite material of step (1) in a jet mill to obtain expanded graphite / amorphous carbon powder;

[0008] (3) mixing the expanded graphite / amorphous carbon powder of step (2) with a metal salt solution of a transition metal element to prepare an expanded graphite / amorphous carbon / transition metal ion composite;

[0009] (4) under a protective atmosphere, mixing the expanded graphite / amorphous carbon / transition metal ion composite of step (3) with a sulfur source, reacting to prepare an expanded graphite / amorphous carbon / transition metal sulfide composite material;

[0010] (5) Mixing the expanded graphite / amorphous carbon / transition metal sulfide composite material of step (4) with a coating agent and performing a carbonization treatment to prepare the expanded graphite-based composite negative electrode material.

[0011] According to an embodiment of the present invention, in step (1), the expanded graphite is worm-shaped, and the expanded graphite has a four-level pore structure, wherein the first-level pore structure is a surface-type open pore with a size of about tens of microns to hundreds of microns; the second-level pore structure is a willow-leaf-shaped pore between sub-lamellar layers, which is mutually interconnected laterally and has a size of about several microns to tens of microns; the third-level pore structure is a polygonal pore within the sub-lamellar layer with a size of about 100nm-600nm; and the fourth-level pore structure is located on the pore wall of the third-level pore.

[0012] According to an embodiment of the present invention, in step (1), the interlayer spacing d(002) of the (002) crystal plane of the expanded graphite is 0.34nm-0.42nm, for example, 0.34nm, 0.35nm, 0.36nm, 0.37nm, 0.38nm, 0.39nm, 0.40nm, 0.41nm or 0.42nm.

[0013] According to an embodiment of the present invention, in step (1), the expanded graphite can be prepared by methods known in the art, or purchased through commercial channels.

[0014] According to an embodiment of the present invention, in step (1), the aromatic hydrocarbon substance is selected from one or more of naphthalene, anthracene, phenanthrene, pyrene, coumarone resin and petroleum resin.

[0015] According to an embodiment of the present invention, in step (1), the mass ratio of the aromatic hydrocarbon substance to the expanded graphite is (1-5):1, for example, 1:1, 2:1, 3:1, 4:1 or 5:1.

[0016] According to an embodiment of the present invention, in step (1), the ball milling mixing time is 1-5 hours, for example, 2 hours, 3 hours or 4 hours; the ball milling mixing speed is 100-400 rpm, for example, 100 rpm, 200 rpm, 300 rpm or 400 rpm.

[0017] According to an embodiment of the present invention, in step (1), the polymerization reaction temperature is 150-300°C, for example, 150°C, 200°C, 250°C or 300°C; the polymerization reaction time is 1-10 hours, for example, 1 hour, 2 hours, 3 hours, 5 hours, 6 hours, 8 hours or 10 hours.

[0018] According to an embodiment of the present invention, in step (1), 10-30 ml of boron trifluoride gas is introduced per gram of aromatic hydrocarbon substance, for example, 10 ml, 12 ml, 15 ml, 18 ml, 20 ml, 22 ml, 24 ml, 25 ml, 28 ml or 30 ml of boron trifluoride gas is introduced per gram of aromatic hydrocarbon substance.

[0019] According to an embodiment of the present invention, in step (1), during the polymerization reaction, the aromatic hydrocarbon substance in a molten state enters the interlayer structure inside the expanded graphite, and boron trifluoride catalyzes the aromatic hydrocarbon substance to undergo a condensation reaction to generate a high molecular weight macromolecular polymer. The generated macromolecular polymer will be transformed into amorphous carbon during the carbonization process, which fills the defects of the interlayer structure of the expanded graphite, enhances the bonding force between the layers of the expanded graphite, avoids the defects of partial decomposition, reorganization and structural changes of the internal structure of the expanded graphite under the influence of stress after multiple charge and discharge cycles, and can significantly improve the stability of the expanded graphite.

[0020] According to an embodiment of the present invention, in step (1), the temperature of the carbonization treatment is 450-650°C, for example, 450°C, 500°C, 550°C, 600°C or 650°C; the time of the carbonization treatment is 1-5 hours, for example, 2 hours, 3 hours or 4 hours.

[0021] According to an embodiment of the present invention, in step (1), after the carbonization treatment is completed, the carbonized material is preferably cooled to room temperature to prepare an expanded graphite / amorphous carbon composite material.

[0022] According to an embodiment of the present invention, in step (1), the expanded graphite and the aromatic hydrocarbon material are ball-milled and mixed, and then the mixture is added to a reactor and heated to 150-300° C. for polymerization reaction, and boron trifluoride gas is introduced into the reactor at the same time. After the polymerization reaction is completed, nitrogen is introduced into the reactor, and the temperature is further raised to 450-650° C. in a nitrogen atmosphere for carbonization treatment to prepare an expanded graphite / amorphous carbon composite material.

[0023] According to an embodiment of the present invention, in step (2), the air flow pulverizer is a air flow pulverizer known in the art.

[0024] According to an embodiment of the present invention, in step (2), the first-order pore structure and the second-order pore structure of the expanded graphite can be cut off during the pulverization process, thereby exposing the third-order pore structure and the fourth-order pore structure, thereby increasing the specific surface area of ​​the expanded graphite, which is beneficial to the adsorption and formation of transition metal sulfides in the subsequent preparation process.

[0025] According to an embodiment of the present invention, in step (2), the median particle size D of the expanded graphite / amorphous carbon powder is 50 8-25 μm, for example, 10 μm, 12 μm, 15 μm, 18 μm or 20 μm.

[0026] According to an embodiment of the present invention, in step (3), the transition metal element is at least one of tin, antimony, cobalt, iron, zinc, molybdenum and manganese.

[0027] According to an embodiment of the present invention, in step (3), the metal salt of the transition metal element is at least one of the nitrate, carbonate, sulfate and chloride of the transition metal element.

[0028] According to an embodiment of the present invention, in step (3), the concentration of the metal salt solution of the transition metal element is 1-5 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L.

[0029] According to an embodiment of the present invention, in step (3), the mass ratio of the expanded graphite / amorphous carbon powder to the metal salt solution of the transition metal element is 1:5-1:10, for example, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10.

[0030] According to an embodiment of the present invention, in step (3), the mixing is carried out under stirring conditions.

[0031] According to an embodiment of the present invention, in step (3), during the mixing process, the transition metal ions are adsorbed into the pores of the expanded graphite / amorphous carbon powder (specifically expanded graphite).

[0032] According to an embodiment of the present invention, in step (3), after the mixing is completed, the mixed solution is preferably filtered, washed and dried to obtain an expanded graphite / amorphous carbon / transition metal ion composite.

[0033] According to an embodiment of the present invention, in step (4), the protective atmosphere is, for example, a nitrogen atmosphere or an argon atmosphere.

[0034] According to an embodiment of the present invention, in step (4), the reaction temperature is 300-900°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C; the reaction time is 1-6 hours, for example, 1 hour, 2 hours, 3 hours, 5 hours or 6 hours.

[0035] According to an embodiment of the present invention, in step (4), the sulfur source is selected from at least one of thioacetamide, ammonium persulfate, thiourea and sodium sulfide.

[0036] According to an embodiment of the present invention, in step (4), the mass ratio of the expanded graphite / amorphous carbon / transition metal ion composite to the sulfur source is 1:(5-10), for example, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10.

[0037] According to an embodiment of the present invention, in step (4), during the reaction process, the transition metal ions react with the sulfur source to generate transition metal sulfides, which are loaded into the pores of the expanded graphite, which not only effectively overcomes the agglomeration of the transition metal sulfides, but also improves the capacity of the prepared expanded graphite-based composite negative electrode material.

[0038] According to an embodiment of the present invention, in step (5), the coating agent is selected from one or more of coumarone resin, phenolic resin, glucose and epoxy resin.

[0039] According to an embodiment of the present invention, in step (5), the mass ratio of the coating agent to the expanded graphite / amorphous carbon / transition metal sulfide composite material of step (4) is (3-10):100, for example, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100 or 10:100.

[0040] According to an embodiment of the present invention, in step (5), the temperature of the carbonization treatment is 800-1000°C, for example, 800°C, 850°C, 900°C, 950°C or 1000°C; the time of the carbonization treatment is 1-6 hours, for example, 1 hour, 2 hours, 3 hours, 5 hours or 6 hours.

[0041] According to an embodiment of the present invention, in step (5), the carbonization treatment is carried out in a nitrogen atmosphere or an argon atmosphere.

[0042] According to an embodiment of the present invention, in step (5), after the carbonization treatment is completed, the carbonization product is preferably dispersed to obtain a median particle size D 50 The invention relates to an expanded graphite-based composite negative electrode material with a particle size of 8-25 μm.

[0043] According to an embodiment of the present invention, in step (5), the coating agent can be coated on the outer surface of the expanded graphite / amorphous carbon / transition metal sulfide composite material, and the coating agent will form a hard carbon layer after carbonization treatment. The presence of the hard carbon layer can further stabilize the structure of the inner core (expanded graphite / amorphous carbon / transition metal sulfide composite material) to ensure the stable performance of the expanded graphite-based composite negative electrode material during the charge and discharge process.

[0044] The present invention also provides an expanded graphite-based composite negative electrode material prepared by the method.

[0045] According to an embodiment of the present invention, the expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, the core is a composite material of expanded graphite / transition metal sulfide / amorphous carbon, the amorphous carbon fixes the transition metal sulfide in the pores of the expanded graphite, and the shell layer is hard carbon.

[0046] According to an embodiment of the present invention, the median particle size D of the expanded graphite-based composite negative electrode material is 50 8-25 μm, for example, 10 μm, 12 μm, 15 μm, 18 μm or 20 μm.

[0047] According to an embodiment of the present invention, the mass ratio of expanded graphite to transition metal sulfide in the expanded graphite-based composite negative electrode material is 100:(5-15), for example, 100:5, 100:6, 100:8, 100:10, 100:12 or 100:15. If the content of transition metal sulfide is too high (such as greater than 100:15), the cycle stability of the negative electrode material will be affected; if the content of transition metal sulfide is too low (such as less than 100:5), the capacity improvement effect of the obtained negative electrode material is not obvious.

[0048] According to an embodiment of the present invention, the mass ratio of expanded graphite to amorphous carbon in the expanded graphite-based composite negative electrode material is 100:(1-5), for example, 100:1, 100:2, 100:3, 100:4 or 100:5.

[0049] According to an embodiment of the present invention, the mass ratio of expanded graphite to hard carbon in the expanded graphite-based composite negative electrode material is 100:(1-4), for example, 100:1, 100:2, 100:3 or 100:4.

[0050] The present invention also provides the use of the expanded graphite-based composite negative electrode material, which is used in lithium ion batteries, preferably used to prepare negative electrodes of lithium ion batteries.

[0051] The present invention also provides a negative electrode for a lithium ion battery, wherein the negative electrode comprises the above-mentioned expanded graphite-based composite negative electrode material.

[0052] The present invention also provides a lithium ion battery, which comprises the above-mentioned expanded graphite-based composite negative electrode material or the above-mentioned negative electrode for a lithium ion battery.

[0053] Beneficial effects of the present invention:

[0054] The present invention firstly utilizes low-melting-point aromatic hydrocarbon substances to enter the interlayer structure inside the expanded graphite in a molten state, and while catalyzing the polymerization of the aromatic hydrocarbon substances by boron trifluoride, firmly fixes amorphous carbon (a product of a polymer formed by the polymerization of the aromatic hydrocarbon substances after carbonization) between the expanded graphite layers, thereby filling the defects of the interlayer structure of the expanded graphite, enhancing the bonding force between the expanded graphite layers, avoiding the defects of partial decomposition, reorganization and structural change of the internal structure of the expanded graphite under the influence of stress after multiple charge and discharge cycles, and significantly improving the stability of the expanded graphite, thereby improving the cycle performance and rate performance of the expanded graphite-based composite negative electrode material. The third and fourth pore structures of the expanded graphite are exposed by crushing to increase the specific surface area of ​​the expanded graphite; then it is immersed in a metal salt solution containing transition metal elements to adsorb transition metal ions into the pores of the expanded graphite; then it reacts with a sulfur source at high temperature to generate transition metal sulfides; the transition metal sulfides are loaded into the pores of the expanded graphite, which not only effectively overcomes the agglomeration of transition metal sulfides, but also increases the capacity of the prepared expanded graphite-based composite negative electrode material. Finally, a hard carbon layer is coated on its surface, and the presence of the hard carbon layer can stabilize the structure of the inner core and ensure the stable performance of the expanded graphite-based composite negative electrode material during the charge and discharge process.

[0055] The present invention uses transition metal sulfide as an active material, which has an ultra-high theoretical capacity and a low preparation cost. The present invention cleverly loads the transition metal sulfide into the pores of expanded graphite, which not only effectively overcomes the agglomeration of transition metal sulfide, but also solves the problem of poor cycle performance of transition metal sulfide. The expanded graphite-based composite negative electrode material has high capacity, cycle performance and rate performance. DETAILED DESCRIPTION

[0056] The method of the present invention will be described in further detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0057] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0058] The shape of the expanded graphite used in the following examples and comparative examples is spherical, and the interlayer spacing d(002) of the (002) crystal plane of the expanded graphite used in the following examples and comparative examples is 0.39 nm.

[0059] Example 1

[0060] (1) After 10 g of expanded graphite and 40 g of naphthalene were ball-milled and mixed (300 rpm) for 5 hours, the mixture was placed in a reactor and heated to 240° C., and then 800 ml of boron trifluoride gas was introduced into the reactor. After polymerization for 8 hours, nitrogen was introduced, and the temperature was further raised to 480° C. After being kept at this temperature for 4 hours, the mixture was cooled to room temperature to prepare an expanded graphite / amorphous carbon composite material;

[0061] (2) 10 g of expanded graphite / amorphous carbon composite material was crushed and classified in a jet mill to obtain a median particle size D 50 12μm expanded graphite / amorphous carbon powder;

[0062] (3) adding 10 g of zinc chloride solution (4 mol / L) to 1 g of expanded graphite / amorphous carbon powder, stirring for 6 hours, filtering, washing, and drying to obtain an expanded graphite / amorphous carbon / zinc ion composite;

[0063] (4) mixing 1 g of the expanded graphite / amorphous carbon / transition metal ion composite of step (3) with 9 g of thiourea, heating to 600° C. under a nitrogen atmosphere and keeping the temperature for 5 h to prepare an expanded graphite / amorphous carbon / zinc sulfide composite material;

[0064] (5) 1 g of the expanded graphite / amorphous carbon / zinc sulfide composite material of step (4) was mixed with 0.07 g of phenolic resin, and carbonized at 900° C. for 6 hours under a nitrogen atmosphere to obtain the expanded graphite-based composite negative electrode material.

[0065] The expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, the core is selected from a composite material of expanded graphite / amorphous carbon / zinc sulfide, the amorphous carbon fixes the transition metal sulfide in the pores of the expanded graphite, and the shell layer is hard carbon; in the expanded graphite-based composite negative electrode material, the mass ratio of expanded graphite: zinc sulfide: amorphous carbon: hard carbon is 100:12:4.2:3.4.

[0066] Example 2

[0067] (1) After 10 g of expanded graphite and 15 g of anthracene were ball-milled (150 rpm) for 3 hours, the mixture was placed in a reactor and heated to 160° C., and then 150 ml of boron trifluoride gas was introduced into the reactor. After polymerization for 4 hours, nitrogen was introduced and the temperature was further raised to 550° C. After being kept at this temperature for 4 hours, the mixture was cooled to room temperature to prepare an expanded graphite / amorphous carbon composite material;

[0068] (2) 10 g of expanded graphite / amorphous carbon composite material was crushed and classified in a jet mill to obtain a median particle size D 50 12μm expanded graphite / amorphous carbon powder;

[0069] (3) adding 10 g of tin chloride solution (1 mol / L) to 1 g of expanded graphite / amorphous carbon powder, stirring for 5 hours, filtering, washing, and drying to obtain an expanded graphite / amorphous carbon / tin ion composite;

[0070] (4) mixing 1 g of the expanded graphite / amorphous carbon / tin ion composite of step (3) with 5 g of thioacetamide, heating to 550° C. under a nitrogen atmosphere and keeping the temperature for 5 h to prepare an expanded graphite / amorphous carbon / tin sulfide composite material;

[0071] (5) 1 g of the expanded graphite / amorphous carbon / tin sulfide composite material of step (4) was mixed with 0.04 g of phenolic resin, and carbonized at 850° C. for 8 hours under a nitrogen atmosphere to obtain the expanded graphite-based composite negative electrode material.

[0072] The expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, the core is selected from a composite material of expanded graphite / amorphous carbon / tin sulfide, the amorphous carbon fixes transition metal sulfides in the pores of the expanded graphite, and the shell layer is hard carbon; in the expanded graphite-based composite negative electrode material, the mass ratio of expanded graphite: tin sulfide: amorphous carbon: hard carbon is 100:6.7:2.2:2.1.

[0073] Example 3

[0074] (1) 10 g of expanded graphite and 30 g of naphthalene were ball-milled and mixed (300 rpm) for 2 hours, then placed in a reactor and heated to 200° C., and then 600 ml of boron trifluoride gas was introduced into the reactor. After polymerization for 7 hours, nitrogen was introduced, and the temperature was further raised to 510° C. After being kept at this temperature for 5 hours, the mixture was cooled to room temperature to prepare an expanded graphite / amorphous carbon composite material.

[0075] (2) 10 g of expanded graphite / amorphous carbon composite material was crushed and classified in a jet mill to obtain a median particle size D 50 12μm expanded graphite / amorphous carbon powder;

[0076] (3) adding 10 g of cobalt chloride solution (3 mol / L) to 1 g of expanded graphite / amorphous carbon powder, stirring for 6 hours, filtering, washing, and drying to obtain an expanded graphite / amorphous carbon / cobalt ion composite;

[0077] (4) mixing 1 g of the expanded graphite / amorphous carbon / cobalt ion composite of step (3) with 8 g of thiourea, heating to 600° C. under a nitrogen atmosphere and keeping the temperature for 5 h to prepare an expanded graphite / amorphous carbon / cobalt sulfide composite material;

[0078] (5) 1 g of the expanded graphite / amorphous carbon / cobalt sulfide composite material of step (4) was mixed with 0.1 g of epoxy resin, and carbonized at 900° C. for 6 hours under a nitrogen atmosphere to obtain the expanded graphite-based composite negative electrode material.

[0079] The expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, the core is selected from a composite material of expanded graphite / amorphous carbon / cobalt sulfide, the amorphous carbon fixes the transition metal sulfide in the pores of the expanded graphite, and the shell layer is hard carbon; in the expanded graphite-based composite negative electrode material, the mass ratio of expanded graphite: cobalt sulfide: amorphous carbon: hard carbon is 100:9.6:3.4:3.8.

[0080] Example 4

[0081] (1) 10 g of expanded graphite and 50 g of naphthalene were ball-milled and mixed (350 rpm) for 4 hours, then placed in a reactor and heated to 180° C., then 1300 ml of boron trifluoride gas was introduced into the reactor, and after polymerization for 10 hours, nitrogen was introduced, and the temperature was further raised to 540° C., kept at this temperature for 4 hours, and then cooled to room temperature to prepare an expanded graphite / amorphous carbon composite material;

[0082] (2) 10 g of expanded graphite / amorphous carbon composite material was crushed and classified in a jet mill to obtain a median particle size D 50 12μm expanded graphite / amorphous carbon powder;

[0083] (3) adding 10 g of zinc chloride solution (5 mol / L) to 1 g of expanded graphite / amorphous carbon powder, stirring for 6 hours, filtering, washing, and drying to obtain an expanded graphite / amorphous carbon / zinc ion composite;

[0084] (4) mixing 1 g of the expanded graphite / amorphous carbon / zinc ion composite of step (3) with 10 g of thiourea, heating to 600° C. under a nitrogen atmosphere and keeping the temperature for 5 h to prepare an expanded graphite / amorphous carbon / zinc sulfide composite material;

[0085] (5) 1 g of the expanded graphite / amorphous carbon / zinc sulfide composite material of step (4) was mixed with 0.08 g of phenolic resin, and carbonized at 900° C. for 6 hours under a nitrogen atmosphere to obtain the expanded graphite-based composite negative electrode material.

[0086] The expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, the core is selected from a composite material of expanded graphite / amorphous carbon / zinc sulfide, the amorphous carbon fixes the transition metal sulfide in the pores of the expanded graphite, and the shell layer is hard carbon; in the expanded graphite-based composite negative electrode material, the mass ratio of expanded graphite: zinc sulfide: amorphous carbon: hard carbon is 100:14.5:4.3:3.6.

[0087] Comparative Example 1

[0088] (1) 10 g of expanded graphite was crushed and classified in a jet mill to obtain a median particle size D 50 12μm expanded graphite powder;

[0089] (2) adding 10 g of zinc chloride solution (4 mol / L) to 1 g of expanded graphite, stirring for 6 hours, filtering, washing, and drying to obtain an expanded graphite / zinc ion composite;

[0090] (3) mixing 1 g of the expanded graphite / transition metal ion composite of step (2) with 9 g of thiourea, heating to 600° C. under a nitrogen atmosphere and keeping the temperature for 5 h to prepare an expanded graphite / zinc sulfide composite material;

[0091] (4) 1 g of the expanded graphite / zinc sulfide composite material of step (3) and 0.07 g of phenolic resin were mixed, and carbonized at 900° C. for 6 hours under a nitrogen atmosphere to prepare the expanded graphite-based composite negative electrode material.

[0092] The expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, the core is selected from an expanded graphite / zinc sulfide composite material, the transition metal sulfide is loaded in the pores of the expanded graphite, and the shell layer is hard carbon; in the expanded graphite-based composite negative electrode material, the mass ratio of expanded graphite: zinc sulfide: hard carbon is 100:13.8:5.3.

[0093] Electrochemical performance test:

[0094] Semi-electric test method: The expanded graphite-based composite negative electrode material prepared in the embodiment and comparative example: conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 95:1:1.5:2.5 (mass ratio) was mixed evenly and applied on the copper foil. The coated electrode was placed in a 120°C vacuum drying oven for 12 hours. The simulated battery assembly was carried out in a Braun glove box protected by argon gas. The electrolyte was 1M-LiPF6+EC:DEC:DMC (volume ratio was 1:1:1), and the metal lithium sheet was the counter electrode. The simulated battery test was carried out in a 5V, 1000mA Xinwei battery test cabinet. The charge and discharge voltage was 0.01-1.5V, and the charge and discharge rate was 0.1C. The 0.1C first discharge capacity and 0.1C first coulomb efficiency obtained by the test were listed in Table 1.

[0095] Full battery test method: The expanded graphite-based composite negative electrode material prepared in the embodiment and the comparative example is used as the negative electrode, lithium cobalt oxide is used as the positive electrode, and 1M-LiPF6+EC:DEC:DMC (volume ratio 1:1:1) solution is used as the electrolyte to assemble a full battery, and the charge and discharge at room temperature are carried out at a rate of 1C, and the voltage range is 3.0-4.2V. The cycle performance (capacity retention rate of 300 cycles at room temperature 1C) obtained by the test is listed in Table 1. Rate performance: 0.5, 1, 2, 4 and 6 A·g are experienced in sequence. -1 After the current density reached 0.5 A g -1 When testing capacity, efficiency is maintained.

[0096] Table 1 Electrochemical performance test results

[0097]

[0098] Compared with Example 1, Comparative Example 1 does not add low-melting-point aromatic hydrocarbons for treatment, and amorphous carbon cannot be formed between the expanded graphite layers, resulting in weak binding force of the expanded graphite interlayer structure. After multiple charge and discharge cycles, the expanded graphite is under the influence of stress, and the internal structure of the expanded graphite is partially decomposed, reorganized, and structurally changed, resulting in reduced stability of the expanded graphite matrix, and the expansion of the transition metal sulfide cannot be alleviated. Therefore, the cycle performance and rate performance of the prepared expanded graphite-based composite negative electrode material are significantly reduced.

[0099] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an expanded graphite-based composite negative electrode material, the method comprising the following steps: (1) ball-milling and mixing expanded graphite and aromatic hydrocarbons, then adding the mixture into a reactor for polymerization reaction, while introducing boron trifluoride gas into the reactor, introducing nitrogen into the reactor after the polymerization reaction, and performing carbonization treatment under a nitrogen atmosphere to prepare an expanded graphite / amorphous carbon composite material; (2) crushing and classifying the expanded graphite / amorphous carbon composite material of step (1) in a jet mill to obtain expanded graphite / amorphous carbon powder; (3) mixing the expanded graphite / amorphous carbon powder of step (2) with a metal salt solution of a transition metal element to prepare an expanded graphite / amorphous carbon / transition metal ion composite; (4) under a protective atmosphere, mixing the expanded graphite / amorphous carbon / transition metal ion composite of step (3) with a sulfur source, reacting to prepare an expanded graphite / amorphous carbon / transition metal sulfide composite material; (5) Mixing the expanded graphite / amorphous carbon / transition metal sulfide composite material of step (4) with a coating agent and performing a carbonization treatment to prepare the expanded graphite-based composite negative electrode material.

2. The method according to claim 1, wherein: In step (1), the interlayer spacing d(002) of the (002) crystal plane of the expanded graphite is 0.34 nm-0.42 nm; And / or, in step (1), the aromatic hydrocarbon substance is selected from one or more of naphthalene, anthracene, phenanthrene, pyrene, coumarone resin and petroleum resin; And / or, in step (1), the mass ratio of the aromatic hydrocarbon substance to the expanded graphite is (1-5):1; And / or, in step (1), the polymerization reaction temperature is 150-300° C.; the polymerization reaction time is 1-10 hours; And / or, in step (1), 10-30 ml of boron trifluoride gas is introduced per gram of aromatic hydrocarbon substance; And / or, in step (1), the temperature of the carbonization treatment is 450-650° C.; the time of the carbonization treatment is 1-5 hours.

3. The method according to claim 1 or 2, wherein: In step (2), the median particle size D of the expanded graphite / amorphous carbon powder is 50 8-25μm.

4. The method according to any one of claims 1 to 3, wherein: In step (3), the transition metal element is at least one of tin, antimony, cobalt, iron, zinc, molybdenum and manganese; And / or, in step (3), the concentration of the metal salt solution of the transition metal element is 1-5 mol / L; And / or, in step (3), the mass ratio of the expanded graphite / amorphous carbon powder to the metal salt solution of the transition metal element is 1:5-1:

10.

5. The method according to any one of claims 1 to 4, wherein: In step (4), the reaction temperature is 300-900° C. and the reaction time is 1-6 hours; And / or, in step (4), the sulfur source is selected from at least one of thioacetamide, ammonium persulfate, thiourea and sodium sulfide; And / or, in step (4), the mass ratio of the expanded graphite / amorphous carbon / transition metal ion composite to the sulfur source is 1:(5-10).

6. The method according to any one of claims 1 to 5, wherein: In step (5), the coating agent is selected from one or more of coumarone resin, phenolic resin, glucose and epoxy resin; And / or, in step (5), the mass ratio of the coating agent to the expanded graphite / amorphous carbon / transition metal sulfide composite material of step (4) is (3-10):100; And / or, in step (5), the temperature of the carbonization treatment is 800-1000° C.; the time of the carbonization treatment is 1-6 hours.

7. An expanded graphite-based composite negative electrode material prepared by the method according to any one of claims 1 to 6.

8. The expanded graphite-based composite negative electrode material according to claim 7, wherein: The expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, wherein the core is a composite material of expanded graphite / transition metal sulfide / amorphous carbon, the amorphous carbon fixes the transition metal sulfide in the pores of the expanded graphite, and the shell layer is hard carbon. Preferably, the mass ratio of expanded graphite to transition metal sulfide in the expanded graphite-based composite negative electrode material is 100:(5-15); and / or, the mass ratio of expanded graphite to amorphous carbon in the expanded graphite-based composite negative electrode material is 100:(1-5); and / or, the mass ratio of expanded graphite to hard carbon in the expanded graphite-based composite negative electrode material is 100:(1-4).

9. A negative electrode for a lithium ion battery, comprising the expanded graphite-based composite negative electrode material according to claim 7 or 8.

10. A lithium ion battery, comprising the expanded graphite-based composite negative electrode material according to claim 7 or 8 or the negative electrode for a lithium ion battery according to claim 9.